Traces of Cultural Osmosis in Jangjawokan Paranti Melet - Peri Sandi (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2026)
Previous studies on Jangjawokan have primarily examined it as a form of mantra, with limited attention to its role as a cultural knowledge system that reflects broader social and cosmological dynamics. This article examines three texts of Jangjawokan paranti melet to explore their internal logic, triadic structure, and mechanisms of cultural adaptation. The study aims to explain how these textual features reflect Tritangtu cosmology and illustrate processes of cultural osmosis within Sundanese tradition. A qualitative-interpretative method with a hermeneutic approach was employed by drawing on Clifford Geertz’s concept of thick description, Jakob Sumardjo’s Tritangtu cosmology, and Denys Lombard’s theory of cultural osmosis. The results indicate that Jangjawokan serves not only as a ritual expression but also as a symbolic system through which intentions and emotional relationships are conveyed within a cosmological context. The identified triadic structure, consisting of invocation, personification, and affirmation, reflects Tritangtu principles while indicating processes of cultural osmosis through the absorption and reinterpretation of pre-Hindu, Hindu-Buddhist, and Islamic elements. This study contributes to extending the interpretation of Jangjawokan beyond textual ritual practices toward understanding it as a dynamic cultural knowledge system and suggests further ethnographic and comparative exploration of related oral traditions.